Numerical simulation of dynamic interactions between two cracks originating from adjacent boreholes in the opposite directions during supercritical CO2 fracturing coal mass. (January 2020) - Yan, Hao; Zhang, Jixiong; Zhou, Nan; Li, Meng; Suo, Yu
Highlights: A staged numerical simulation method of SC-CO2 fracturing was proposed. Dynamic interactions between two cracks originating from adjacent fracturing boreholes were studied. The influence of horizontal and vertical distances of adjacent fracturing boreholes on crack propagation was discussed. The fracturing borehole layout process of SC-CO2 fracturing coal mass was proposed. Abstract: As an environmentally waterless fracturing technology, supercritical carbon dioxide (SC-CO2 ) fracturing technology is gaining more and more attention in the process of safe mining of coal resources. Based on the phase change of CO2 in the fracturing process, a staged numerical simulation method of SC-CO2 fracturing considering the change of CO2 phase was proposed, and the fluid-solid coupling numerical model of adjacent fracturing boreholes in SC-CO2 fracturing was constructed. The dynamic interactions between two cracks originating from adjacent fracturing boreholes in the opposite directions were studied, and the influence of horizontal and vertical distances of adjacent fracturing boreholes on crack propagation was also discussed. The results indicated that the propagation process of two cracks initiated in the coal mass boreholes can be subdivided into three stages: (i) independent propagation, (ii) mutual repulsion, and (iii) mutual attraction. The crack propagation presents the characteristics of "the crack tip repels the crack tip, and the crack tip attracts the propagated crack surface". The larger the vertical distance or horizontal distance of adjacent fracturing boreholes, the larger the crack propagation length, but the less the stress interference degree of the opposite cracks. In the design of fracturing parameters, it is necessary to ensure that the crack propagation length is large enough, and also requires the use of "stress interference" to form complex crack network. Finally, based on the research results, the fracturing borehole layout process of SC-CO2 fracturing coal mass was proposed, which can provide a basis for engineering practice of SC-CO2 fracturing.